AS CADEIAS CURTAS DAS FEIRAS COLONIAIS E AGROECOLÓGICAS: AUTOCONSUMO E SEGURANÇA ALIMENTAR E NUTRICIONAL - Luciana Pozzebon (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
This paper analyzes the extent to which colonial and agro-ecology fairs in the city of Chapecó, State of Santa Catarina (SC), Brazil, allow the self-consumption of farming families and hence its contribution to the aspects related to their food and nutrition security (SAN). The study is justified by the contributions they can make the safety actions and policies food and nutrition and rural development. This is a cross-sectional and descriptive study with a qualitative approach, using quantitative methods to express the results. This study was carried out with seven farmers marketing in three agricultural fairs in Chapecó. Data were collected from December 2014 to January 2015 using semi-structured interviews and data analysis with descriptive statistics and content analysis. Results show that the self-consumption is recurrent practice among farmers fair dealers. Thus, it is concluded that the farmers’ families follow the food and nutrition security parameters, practicing the self-consumption with easy access to quality and diverse food in sufficient quantity to the family. At the same time, the agricultural fairs proved to be an important strategy for generating income.